Cancer Proteomics From Bench to Bedside - Daoud, Sayed S.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Over the past 20 years or so, there have been tremendous advances in our understanding of how normal cells transform to cancer and the importance of signaling pathways in cancer initiation and progression. Therefore, proteomics technologies must be improved for more global analysis of protein content of cells, tissues and body fluids as well as the posttranslational modifications to allow for proper detections and validation. In Cancer Proteomics, the authors collectively provide the current status of proteomics in cancer therapy and offers the existing technologies used in proteomics that allow for protein profiling and for the identification of druggable targets in human samples. Mass spectrometry based protein characterization and protein microarrays hold great promise of predicting response to specific drugs in cancer therapy. Insightful to the reader with broad perspectives on topics related to the use of proteomic strategies in cancer therapy, Cancer Proteomics offers anticipated challenges that may arise from its application in daily practice.
Proteomics Technologies -- Current and Emerging Mass Spectrometry Instrumentation and Methods for Proteomic Analyses -- Cell Signaling Proteomics -- Integration of Genomics and Proteomics in Dissecting p53 Signaling -- Proteomic Profiling of Tyrosine Kinases as Pharmacological Endpoints for Targeted Cancer Therapy -- Tumor Proteomics -- Oncoproteomics for Personalized Management of Cancer -- Application of Serum and Tissue Proteomics to Understand and Detect Solid Tumors -- Insight on Renal Cell Carcinoma Proteome -- Proteomics in Lung Cancer -- Proteomic Strategies of Therapeutic Individualization and Target Discovery in Acute Myeloid Leukemia -- New Tumor Biomarkers -- Bioinformatics and Regulatory Aspects of Proteomics -- Annotating the Human Proteome -- Regulatory Issues in the Co-Development of Oncology Drugs and Proteomic Tests: An Overview.
Keywords: Cancer research; Proteomics; Oncology .; Cancer Research; Proteomics; Oncology